1993
DOI: 10.1007/bf01614765
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of infiltrating cells in human chronic chagasic myocarditis: Comparison with myocardial rejection process

Abstract: Cellular subpopulations that infiltrate the heart in human chronic chagasic myocarditis were defined immunohistochemically in endomyocardial biopsy (EMB) specimens. T cells formed 96.3% of the inflammatory infiltrate, predominantly CD8+ (cytotoxic/suppressor) T cells. The mean numbers of CD8+ and CD4+ (helper) T cells in the myocarditis were compared to those present in the myocardial rejection process. Mean numbers of CD8+ T cells were similar in both groups of EMB specimens while CD4+ T cell counts, CD4+/CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
109
1
17

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 17 publications
10
109
1
17
Order By: Relevance
“…The inflammatory infiltrate found in heart tissue of CCC patients contains macrophages, granzyme-expressing CD8+ T cells, and CD4+ T cells (HIGUCHI et al, 1993). Data from CCC patients show that cytokine profile is shifted towards Finally, work from our group and others has brought to attention the complex role of inflammatory cytokines in CCC pathogenesis.…”
Section: Inflammation and The Role Of Cytokinesmentioning
confidence: 79%
“…The inflammatory infiltrate found in heart tissue of CCC patients contains macrophages, granzyme-expressing CD8+ T cells, and CD4+ T cells (HIGUCHI et al, 1993). Data from CCC patients show that cytokine profile is shifted towards Finally, work from our group and others has brought to attention the complex role of inflammatory cytokines in CCC pathogenesis.…”
Section: Inflammation and The Role Of Cytokinesmentioning
confidence: 79%
“…In CCC, the inflammatory infiltrate is com-posed of macrophages (50%), B cells and T cells (10%) and very few NK cells (Milei et al 1992, Higuchi et al 1993. Also, there is a 2:1 predominance of CD8 + over CD4+ T cells, with increased numbers of granzymepositive cells (Higuchi et al 1993, Reis et al 1993b) and restricted heterogeneity of T cell receptor variable alpha chain transcripts (Cunha-Neto et al 1994), further indicating an antigen-driven inflammatory infiltrate.…”
Section: Pathogenesis: Mononuclear Inflammatory Infiltratementioning
confidence: 99%
“…In CCC, the inflammatory infiltrate is com-posed of macrophages (50%), B cells and T cells (10%) and very few NK cells (Milei et al 1992, Higuchi et al 1993. Also, there is a 2:1 predominance of CD8 + over CD4+ T cells, with increased numbers of granzymepositive cells (Higuchi et al 1993, Reis et al 1993b) and restricted heterogeneity of T cell receptor variable alpha chain transcripts (Cunha-Neto et al 1994), further indicating an antigen-driven inflammatory infiltrate. Several clinicopathological data suggest that the infiltrate plays a major role in the development and progression of the disease: (i) the mononuclear infiltrate is associated with local cardiomyocyte destruction and fibrosis, (ii) CCC presents a shorter survival and worse prognosis than cardiomyopathies of non-inflammatory aetiology, (iii) the frequency of myocarditis in endomyocardial biopsies correlates with the severity of the functional heart damage, being low among asymptomatic individuals with the indeterminate form, intermediate among patients with ECG abnormalities and very frequent (93%) among CCC patients with dilated cardiomyopathy (Higuchi et al 1987) and (iv) we found a positive correlation between the cellularity of the infiltrate and degree of ventricular dilation (unpublished observations) among hamsters chronically infected with T. cruzi.…”
Section: Pathogenesis: Mononuclear Inflammatory Infiltratementioning
confidence: 99%
See 2 more Smart Citations